Effectiveness of STEM-Based Lectora Inspire Media to Improve Students’ HOTS in Physics Learning - Kurniawan, Aziz; Tantri, Irma Dwi; Fian, Khafifatul (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study aimed to determine the effectiveness of STEM-based lectora inspire media to improve the student’s higher order thinking skills (HOTS). This research design was Research and Development (RnD). This research referred to the ADDIE model that included Analysis, Design, Development, Implementation, and Evaluation. The data were gathered through questionnaires and tests. The questionnaire technique was used to test the feasibility of the material and media used. At the same time, the test instrument was used to determine the increase in students’ HOTS based on the final results after using the product. The results showed that the developed media was categorized as feasible to be used as a student learning media with an average score of 93.745% of material expert judgment and 87.485% of media expert judgment. The responses of science teachers and students as users were 91.66% and 87%. Both concluded that the learning media was efficient. Paired sample t-test resulted in a significance value of 0.000 < 0.005, and the N-Gains test yielded a value of 58%. Thus, it can be concluded that STEM-based Lectora Inspire Media can improve the student’s higher order thinking skills (HOTS).